Nitrous oxide and methane emissions from a long-term fertilizer experiment - Palmqvist, Martin (2012)
Because of the increasing concentration of methane (CH4) and nitrous oxide (N2O) in the atmosphere, there is an increasing concern about the emissions of these two gases from agricultural land. Both CH4 and N2O are major contributors to the greenhouse effect and agricultural lands constitute a large contributor of the anthropogenic load of these gases. Agricultural land is also something that will always be needed, so a long term view towards sustainability is needed. In situ measurements of CH4 and N2O emissions were conducted on a long‐term fertilizer experiment in Uppsala. The aim was to compare the emissions from the different fertilizing regimes. The fertilizers investigated were ammonium sulphate ((NH4)2SO4, manure and sewage sludge in comparison to unfertilized plots. The emissions were related to the differences in soil properties and weather conditions at the site at the time of sampling. The emission measurements were constricted two occasions. Negative CH4 emissions indicated that the soils were net sinks and there was no difference between treatments and time points. The two sampling occasions showed slightly different results regarding N2O with higher emissions in February, but there were no statistically significant differences. In April 2008 the sewage sludge amended soil had the highest emissions while the results from February 2009 showed that the manure fertilized soil had highest emissions.